Comparative study of the selection of the best contractor using fuzzy weak autocatalytic set and analytic hierarchy process / Siti Salwana Mamat, Zarith Sofiah Othman and Noraini Ahmad - Mamat, Siti Salwana; Othman, Zarith Sofiah; Ahmad, Noraini (Universiti Teknologi MARA, Perak, 2024)
Pairwise comparisons are commonly used in decision-making procedures, especially when Multiple Criteria Decision Making (MCDM) is involved. Effective techniques are needed to address the problem related to MCDM. Using the Fuzzy Weak Autocatalytic Set (FWACS) method, the pairwise comparisons of alternatives can be represented as a directed graph with fuzzy edges. The objectives of this study are: 1) to explore and apply the FWACS technique in the problem of contractor selection. 2) to compare the outcomes of FWACS with those obtained using the Analytic Hierarchy Process (AHP). To ensure that judgments made with FWACS are stable and consistent, a sensitivity analysis is carried out. The choices reached using FWACS are consistent and stable, thus comparable to AHP. However, FWACS distinguishes itself with its proficiency in handling ambiguity, particularly in the fuzzy framework. This study highlights the necessity of implementing comprehensive and systematic contractor selection criteria to enhance the efficiency and success of construction projects, thereby mitigating the risks associated with inadequate contractor performance.